The potency of recycled aggregate in new concrete: a review. Issue 4 (6th August 2019) - Anike, Emmanuel Ejiofor; Saidani, Messaoud; Ganjian, Eshmaiel; Tyrer, Mark; Olubanwo, Adegoke Omotayo
Abstract : Purpose: This paper aims to review the effect of using recycled aggregates (RA) on the properties of recycled aggregate concrete (RAC) following the steady rise in global demand for concrete and the large generation of construction and demolition waste. Design/methodology/approach: This study reviewed relevant literature of research work carried out by previous researchers, leading to a deeper understanding of the properties of both RA and RAC. The properties of RA and RAC reported in the various studies were then compared to their corresponding natural aggregate (NA) and natural aggregate concrete, as well as the specifications provided in different codes of practice. In addition, the mix design methods appropriate to RAC and the cost implication of using RA were reviewed. Findings: Findings show that the contribution of RA to strength appears inferior in comparison to NA. The shortcoming is attributed to the mortar attached to the RA, which raises its water absorption capacity and lowers its density relative to those of NA. However, it has been reported that the use of regulated quantity of RA, new mixing and proportioning methods, the addition of admixtures and strengthening materials such as steel fibres, can improve both mechanical and durability properties of RAC. Cost evaluation also showed that some savings can be realized by using RA instead of NA. Originality/value: This research serves as a guide for future works and suggests that the use of RA as aggregate in new concrete is technically possible, depending on the mix design method adopted.